The Prospects And Challenges Of Tourism Development In Sarawak - Abas, Said (International Symposium on East Asia Tourism Promotion Toward a New Millennium, Seoul, September 9, 1999, 1999)
Sarawak's tourism industry is still at an infancy stage but has experienced rapid growth over the last decades. This paper is aimed to provide an overview ofthe development in the tourism sector in Sarawak which focus on four (4) major topics including a) its present status, b) policy direction c) role of stakeholders and d) relevant issues and opportunities. This sector has been recognized as a significant contributor to the state's economy toward generating foreign exchange and provides employment opportunities. However, the successful promotion of tourism in Sarawak requires cognizance of a number of issues such as basic infrastructures and accessibility; local participation; product development; environmental and social impacts; application oftechnology and research needs. The East Asian financial crisis which struck in 1997 has also undermined this sector in many countries in the region including Sarawak. Approximately 196,223 foreign tourists arrived in Sarawak in 1997. The total arrivals declined by 6.8%, compared to 210,430 foreign tourists in 1996. In 1997, Sarawak received RM 409.3 million, a decrease of 13.9% from RM 475.6 million recorded in 1996. Nevertheless, the slow-down of the tourism industry is considered temporary in nature as the rapid economic recovery in the region will boost tourism. Tourists from ASEAN countries constitute almost goolo of the total tourists to Sarawak. This sector may become a major contributor and the driving force of Sarawak's economy in future. Sarawak has plenty of tourism resources to offer such as nature and cultural based resources which have yet to be fully explored. Finally, the growth in global tourism market provides opportunities for Sarawak to benefit from the untapped market.